2022
DOI: 10.1111/jre.12981
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones alleviate periodontal destruction in ovariectomized rats

Abstract: Objective The purpose of this study was to investigate whether soy isoflavone supplementation is effective in preventing periodontal destruction exacerbated by estrogen deficiency (ED) and its potential mechanism. Background The progression of periodontitis is affected by host factors, such as smoking, diabetes mellitus, and steroid use. Bone loss in periodontitis can be aggravated by ED. Methods A rat model of experimental periodontitis (EP) with ED was established by silk ligature and inoculation with Porphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…Table 1 summarizes the effect of phytoestrogens against alveolar bone loss. In a recently published study, oral administration of soy isoflavones was found to alleviate experimental periodontitis in estrogen-deficient rats as revealed by the increased expression of tight junction proteins in the gingiva, reduced proinflammatory cytokines, IL-17 and ROS levels (Liu et al, 2022). Attenuation of alveolar bone loss was observed through micro-CT and histologic observation.…”
Section: Effects Of Phytoestrogens On Alveolar Bone Lossmentioning
confidence: 98%
See 1 more Smart Citation
“…Table 1 summarizes the effect of phytoestrogens against alveolar bone loss. In a recently published study, oral administration of soy isoflavones was found to alleviate experimental periodontitis in estrogen-deficient rats as revealed by the increased expression of tight junction proteins in the gingiva, reduced proinflammatory cytokines, IL-17 and ROS levels (Liu et al, 2022). Attenuation of alveolar bone loss was observed through micro-CT and histologic observation.…”
Section: Effects Of Phytoestrogens On Alveolar Bone Lossmentioning
confidence: 98%
“…An in vitro P. gingivalis infection model was also used to determine whether grainyhead-like 2 (GRHL2), the epithelial transcription factor and ER-binding partner (He et al, 2020) is required by soy isoflavones to enhance the oral epithelial barrier. It was found that the enhancement of oral gingival epithelial barrier function by soy isoflavones treatment was partially dependent on GRHL2 (Liu et al, 2022).…”
Section: Effects Of Phytoestrogens On Alveolar Bone Lossmentioning
confidence: 99%
“…The periodontium can be severely destroyed by many oral diseases, including inflammatory processes such as gingivitis and periodontitis, and this lack of knowledge makes it difficult to adequately address these tissue defects from a therapeutic point of view. Since millions of people worldwide are affected by these debilitating diseases, their effective treatment is both a medical and an economic challenge [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%